Inovasi Sistem Terminal Parkir Elektronik (TPE) di Kota Makassar - Jumaisa, Jumaisa; Ansari, Muh. Isa; Masyar, Abdul (Universitas Muhammadiyah Makassar, 2020)
Thiis study aimed to determine the innovation of the staffing information system in the BKPSDM Gowa Regency. The informants in this study whwe 6 people. This study used qualitative with the type of phenomenological. Data collection techniqueswere observation,interviews and documentation.The result of the study showed that the personnel information system in BKPSDM Gowa Regency was quite good and had to be developed further. This could be seen from the innovation of the staffing information system (SIMPEG).The application that had been implemented in Gowa Regency which as a whole had made innovations that made it easy for employees to obtain information, data and various programs by accesing staffing data through simpeg. The application of simpeg innovation in Gowa regency through inputs,processes,output and feedback designed to store all staffing data.Online network in simpeg innovation in gowa Regency could be done by using an internet connectivity network system, LAN and quota access that made it easy for employees to access staffing information.